2021
DOI: 10.7883/yoken.jjid.2020.806
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of<i> bla</i><sub>NDM-1</sub> in a Clinical Isolate of <i>Acinetobacter lwoffii</i> in Japan: Comparison of<i> bla</i><sub>NDM-1</sub>-Harboring Plasmids between <i>A. lwoffii</i> and <i>A. pittii</i> Originated from a Hospital Sink

Abstract: Occurrence of blaNDM-1 in a clinical isolate of Acinetobacter lwoffii in Japan: comparison of blaNDM-1-harboring plasmids between A. lwoffii and A. pittii originated from the hospital sink

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…A recent review listed 33 rep groups (GRs) (Salgado-Camargo et al ., 2020), and we have since described an additional group, GR34 (Liu et al ., 2021). Plasmids carrying clinically-significant antibiotic resistance genes (ARGs) have been reported in A. baumannii (Blackwell and Hall, 2017; Hamidian et al ., 2016; Hamidian and Hall, 2014; Liu et al ., 2015; Nigro and Hall, 2014) and in other Acinetobacter species (Alattraqchi et al ., 2021; Hayashi et al ., 2021; Li et al ., 2021; Silva et al ., 2018; Yang et al ., 2021), clearly indicating their important role in the emergence and transmission of antimicrobial resistance in this genus. Few plasmid groups have been the subject of comparative analyses, so how the remaining types evolve or are distributed, geographically and throughout the Acinetobacter genus, is poorly understood and their genetic structures remain largely undescribed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent review listed 33 rep groups (GRs) (Salgado-Camargo et al ., 2020), and we have since described an additional group, GR34 (Liu et al ., 2021). Plasmids carrying clinically-significant antibiotic resistance genes (ARGs) have been reported in A. baumannii (Blackwell and Hall, 2017; Hamidian et al ., 2016; Hamidian and Hall, 2014; Liu et al ., 2015; Nigro and Hall, 2014) and in other Acinetobacter species (Alattraqchi et al ., 2021; Hayashi et al ., 2021; Li et al ., 2021; Silva et al ., 2018; Yang et al ., 2021), clearly indicating their important role in the emergence and transmission of antimicrobial resistance in this genus. Few plasmid groups have been the subject of comparative analyses, so how the remaining types evolve or are distributed, geographically and throughout the Acinetobacter genus, is poorly understood and their genetic structures remain largely undescribed.…”
Section: Introductionmentioning
confidence: 99%
“…baumannii (Blackwell and Hall, 2017;Hamidian et al, 2016;Hamidian and Hall, 2014;Liu et al, 2015; and in other Acinetobacter species (Alattraqchi et al, 2021;Hayashi et al, 2021;Li et al, 2021;Silva et al, 2018;Yang et al, 2021), clearly indicating their important role in the emergence and transmission of antimicrobial resistance in this genus. Few plasmid groups have been the subject of comparative analyses, so how the remaining types evolve or are distributed, geographically and throughout the Acinetobacter genus, is poorly understood and their genetic structures remain largely undescribed.…”
Section: Introductionmentioning
confidence: 99%
“…A recent review listed 33 rep groups [10], and we have since described an additional group, GR34 [11]. Plasmids carrying clinically significant antibiotic resistance genes (ARGs) have been reported in A. baumannii [12][13][14][15][16] and in other Acinetobacter species [7,8,[17][18][19], clearly indicating their important role in the emergence and transmission of antimicrobial resistance in this genus. Few plasmid groups have been the subject of comparative analyses, so how the remaining types evolve or are distributed, geographically and throughout the Acinetobacter genus, is poorly understood and their genetic structures remain largely undescribed.…”
Section: Introductionmentioning
confidence: 99%
“…14,16 In Africa, several investigators have reported the occurrence of NDM-1 amongst members of enteric bacteria, including Klebsiella species, Enterobacter cloacae, Citrobacter freundii, Serratia marcescens, Acinetobacter baumannii etc. [17][18][19][20][21] in South Africa, Kenya, Ethiopia and other eastern/southern African countries. In Nigeria, NDM-1 has been reported amongst Gram-negative enteric bacteria in various geopolitical zone, including the Southwestern region (Lagos), Northeastern region (Maiduguri), South-southern region (Bayelsa), North-western region (Kano), and South-eastern region (Enugu) of the country [22][23][24][25][26][27][28][29] however, non has reported NDM-1 amongst Gram-positive strains.…”
Section: Introductionmentioning
confidence: 99%